Production of biodiesel from non-edible industrial oilseeds via non-catalytic transesterification - Kwon, Dohee; Choi, Dongho; Kim, Jee Young; Song, Hocheol; Lee, Jaewon; Kwon, Eilhann E. (Industrial crops and products, 2024)
The non-catalytic conversion of non-edible biomass into biodiesel (BD) is the subject of this investigation. Conventional oil extraction from biomass often results in economic and technical inefficiencies. This study suggests a non-catalytic transesterification reaction to directly convert castor seeds into BD in order to overcome these problems. Base-catalysed transesterification of extracted castor seed oil had a BD yield of 84.43 wt% (reaction time: 24 h at 60 ˚C). In contrast, non-catalytic transesterification of castor seed oil produced a BD yield of 93.79 wt%, which completed the reaction in 1 min at 390 ˚C. Thus, using the non-catalytic transesterification approach, we were able to empirically verify the greater conversion efficiency of BD. Additionally, the direct non-catalytic conversion of castor seed to BD achieved a yield of 105.81 wt%, suggesting that substantial oil loss occurs during the extraction process. These findings suggest that the traditional method of converting BD, which involves oil extraction and base-catalysed transesterification, is less efficient and less financially advantageous than directly converting castor seeds into BD. [Display omitted] •Non-catalytic transesterification of castor seed oil yields 93.79 wt% BD.•To minimise the oil loss during extraction step, direct conversion was introduced.•Direct conversion of castor seeds achieved 105.81 wt% BD yield.